Mindfulness-Based Interventions for Pregnant Couples: A Scoping Review of Global Evidence with Implication for Indonesia - Kodriati, Nurul; Widarsih, Rina Eko; Nursholihah, Ummu Fitrotin (Faculty of Psychology, Universitas Gadjah Mada, 2026)
Maternal health and mindfulness are known to influence child development, but the existing research has largely focused on individual interventions. There is a lack of synthesis of couple-based mindfulness approaches, particularly in low- and middle-income contexts, where their relevance may differ. This scoping review synthesizes evidence from 17 peer-reviewed studies on couple-based mindfulness interventions implemented during the pre- and postnatal periods. While all included studies focus on interventions, the evidence is reported using diverse study designs, including randomized controlled trials (RCTs), qualitative studies, and clinical case reports, identified through a PRISMA-guided search of PubMed and Google Scholar. Most structured interventions emphasized emotional and relational well-being and were delivered through in-person workshops or online training. Results showed improvements in stress management, emotional regulation, communication, and relationship satisfaction. Some studies highlight the effectiveness of online formats in enhancing positive emotions, supporting the development of both face-to-face and hybrid models. For Indonesia, where paternal involvement in maternal care remains limited and perinatal mental health support is still developing, this study emphasizes the possibility of the potential of culturally tailored, couple-focused mindfulness programs to enhance maternal well-being and partner support and prepare families for parenthood. Expanding such interventions through blended delivery formats and training local facilitators may increase accessibility and sustainability. These findings can guide future research and inform program and policy design in Indonesia to advance equitable maternal and child health.